The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2003
DOI: 10.1007/s11920-003-0067-4
|View full text |Cite
|
Sign up to set email alerts
|

Hallucinogens: An update

Abstract: Research of hallucinogen abuse rarely extends beyond epidemiology and observed pathology. Even less research has been completed on the special circumstances surrounding the religious use of hallucinogens or on potential therapeutic applications. Rather than offer another basic review on the well-known hazards of illicit hallucinogen use, this paper provides an overview and practice recommendations on compounds the clinician may be less familiar with, such as the botanical plant Salvia divinorum, the drug 3,4-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 40 publications
0
14
0
2
Order By: Relevance
“…The testimonies of psychotherapists who have used MDMA, and the experiences of some of their clients, can be extremely persuasive (Greer and Tolbert 1986;Doblin 2002;Grinspoon and Bakalar 1986;Holland 2001b;Liester et al 1992). Many review or commentary papers have noted that MDMA may have potential as a psychotherapeutic agent (Dumont and Verkes 2006;Halpern 2003;Iversen 2006;Nutt 2006;Parrott 2001;Saunders 1997). There are, however, several crucial issues which need to be addressed before it can be concluded that MDMA has an appropriate pharmacological profile for a therapeutic drug (Tables 1, 2, 3).…”
Section: Discussionmentioning
confidence: 99%
“…The testimonies of psychotherapists who have used MDMA, and the experiences of some of their clients, can be extremely persuasive (Greer and Tolbert 1986;Doblin 2002;Grinspoon and Bakalar 1986;Holland 2001b;Liester et al 1992). Many review or commentary papers have noted that MDMA may have potential as a psychotherapeutic agent (Dumont and Verkes 2006;Halpern 2003;Iversen 2006;Nutt 2006;Parrott 2001;Saunders 1997). There are, however, several crucial issues which need to be addressed before it can be concluded that MDMA has an appropriate pharmacological profile for a therapeutic drug (Tables 1, 2, 3).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in our experiments, both SDE and salvinorin A were not active after oral administration. This observation is intriguing in the light of the fact that Salvia divinorum was consumed by Mazatecs Indians of Oaxaca by chewing fresh leaves which made absorption of salvinorin A possible through the oral mucosa 19 …”
Section: Discussionmentioning
confidence: 99%
“…In 430 B.C., for example, Herodotus documented the practice of the Persians to consider affairs of weight while drunk on alcohol; if they first made a decision while sober, they would later deliberately reconsider it under the influence of wine [64] . Conversely, many deeply spiritual traditional societies have long valued hallucinogenic plants -peyote, psilocybin mushrooms, ayahuasca or iboga -for their entheogenic effects [65][66][67] . One might speculate about countless other possible cultural influences.…”
Section: Color Version Available Onlinementioning
confidence: 99%